Ultrasound diagnosis of pyocolpos - Gandage S; Aironi Vyankatesh; Agarwal Saurabh; Singh Jitendra (Wolters Kluwer Medknow Publications, 2007)
Cystic dilatation of vagina due to genital tract obstruction is rare. the cause of obstruction can be imperforate hymen, transverse vaginal septum and vaginal atresia. We pictographically demonstrate a case of 45 days old infant presenting with abdomino-pelvic cystic mass